Monetary Policy and Inflation in Bangladesh: An Analysis of Lending Rates and Deposit Interest Rates (1990–2022) - Gomathi, Deepika (Journal of Global Economy, Business and Finance, 2026)
One of the major important targets for any developing country like Bangladesh, is to achieve consistently high economic growth. Though there are many factors that affect economic growth, this paper discussed the effect of lending rate and deposit rate on inflation of Bangladesh over specific period. Inflation, lending rate and interest rate or Deposit rate are three important macroeconomic indicators as they play vital role on economic growth of any country. The relation among inflation, landing rate and deposit interest rate of 32 years of Bangladesh is analyzed to determine the effect of lending rate and deposit interest rate on inflation. This study is to investigate how lending rate and deposit interest rate influence the inflation of economy of Bangladesh over the stipulated period. An Ordinary Least Square (OLS) model and unit root test are applied to find out the correlation and co-integration related to the discussed three indicators. The research time series data were collected from 1990 to 2022 from the World Bank data website. A lot of controversies and literatures have earlier analyzed this relationship. In context of Bangladesh, very few studies have been done in this regard. This study is done with an objective to determine the effect of inflation on lending rate of Bank loan and banks’ deposit interest rate in Bangladesh. The inflation, lending rate and deposit interest rate satisfy Dickey Fuller Test. All data are stationery at first difference level. The dependent variable inflation rate is regress with the independent variable interest rate and deposit rate.